Tax Reductions Applicable to Corporate Income Tax in Romania - Elena STĂNCIULESCU (CECCAR Business Review)

(untitled)
After performing all the necessary calculations to determine the tax result and implicitly the corporate income tax, the accounting professionals must know the exemptions applicable in Romania regarding the reduction of certain amounts directly from the calculated corporate income tax. In this article are detailed aspects regarding the amounts that are directly deducted from the corporate income tax, namely a percentage of up to 15% applicable according to Government Emergency Ordinance No. 153/2020, tax reductions representing the tax credit, direct tax withholding of sponsorships or redistribution of the “unused” sponsorship difference, tax exemption of reinvested profit, as well as certain bonuses for good-paying taxpayers.